Social Exchange Among Effeminate Male Students in Senior High Schools in Padang City - Angga Dayu Satria; Erianjoni; Delmira Syafrini; Fatmariza (Yayasan Darussalam Bengkulu, 2026)
This study examines the dynamics of social exchange among male students with feminine gender expression in senior high schools in Padang City, West Sumatra, within a socio-cultural context strongly influenced by Minangkabau values. In this study, the term male students with feminine gender expression refers to participants who identify themselves as male while expressing behaviors, communication styles, or aesthetic preferences commonly associated with femininity. The study focuses on gender expression rather than gender identity or sexual orientation, recognizing these as distinct concepts. Grounded in Social Exchange Theory, this research aims to analyze the forms, influencing factors, and impacts of social exchange within school environments. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participant observation, and documentation across five selected schools. Informants included male students with feminine gender expression, peers, and teachers selected through purposive and snowball sampling. Data were analyzed using the Miles and Huberman interactive model. The findings reveal three forms of social exchange: symbolic, emotional, and instrumental. Symbolic exchange involves communication styles, identity recognition, and expressive language; emotional exchange includes empathy, trust, and peer support; while instrumental exchange is reflected in the use of skills and talents to gain acceptance and social recognition. Internal factors, including self-concept, confidence, competencies, and impression management, together with external factors such as peer acceptance, school climate, cultural norms, and social media influence, shape these interactions. The findings indicate that participants actively negotiate their gender expression and build reciprocal social relationships, contributing to their academic engagement, psychological well-being, and social integration within the school community.